1996
DOI: 10.1002/(sici)1097-0096(199605)24:4<179::aid-jcu4>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic “endometrial three‐layer” pattern: A unique finding in ectopic pregnancy

Abstract: Although diagnostic ultrasonography is playing an increasing role in the investigation of the patient with suspected ectopic pregnancy (EP), it has significant limitations in the very early stages of pregnancy.By sonographically exploring the intrauterine echoes in 45 cases of documented EP, we demonstrated a unique pattern in 28 cases (62.2%). A well-defined spheric structure forming an endometrial three-layer (ETL) pattern was seen, probably formed by a midline echo between the two adjacent edematous prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…A previous study showed a sensitivity of 62% for the endometrial three‐layer pattern in the diagnosis of EP. Because the present study would add other variables, a sensitivity of 80% was expected.…”
Section: Methodsmentioning
confidence: 95%
See 4 more Smart Citations
“…A previous study showed a sensitivity of 62% for the endometrial three‐layer pattern in the diagnosis of EP. Because the present study would add other variables, a sensitivity of 80% was expected.…”
Section: Methodsmentioning
confidence: 95%
“…found the trilaminar pattern to be more specific (94%) but less sensitive (38%), with a positive predictive value of 92% and a negative predictive value of 46%. Lavie et al . reported a specificity of 100% and a sensitivity of 62% for the trilaminar pattern, with a positive predictive value of 100% and a negative predictive value of 84%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations